Ethnomathematical Exploration of Numeration Systems: The Mee Tribal Indigenous Community - Ruamba, Marthinus Yohanes; Kho, Ronaldo; Lumbantobing, Happy; Edoway, Naftali (Program Studi Pendidikan IPA FKIP Universitas Jember, 2025)
This study aims at documenting and analyzing the traditional number system of the Mee tribe in Papua within an ethnomathematics framework. Papua is a cultural well with the numeral system reflecting the values of the culture and the social structure of the society. Such integration of culturally based mathematical concepts with the help of the ethnometematic approach might be theoretically expected to enhance mathematical learning, relevant from a cultural point of view. Qualitative research with participatory observation, in-depth interviews, and artifact analysis was carried out in Sentani-Sereh. From the research, it can be said that the uniqueness of the combination between single and decimal numbers can indicate the structure of the Mee Tribe culture. This system shows a possibility for implementation in culture-based learning. This documentation leans more towards cultural preservation efforts, enriching the literature of ethno-mathematics and recognizing traditional knowledge, which is part of cultural heritage and needs to be preserved in the wave of modernization